A Comprehensive Study of Ventilation Tube Insertion in Tympanic Membrane in Sari, Iran 2011-2017 - Payam Habibipour; Mohammad Keshvari; Jila Ganji; Seyed Jafar Motahari Tabari (Journal of Mazandaran University of Medical Sciences, 2021)
Background and purpose: Tympanostomy surgery and ventilation tube (VT) placement are reliable methods to reduce the complications of eustachian tube dysfunction and inadequate middle ear ventilation. However, tympanostomy is associated with some complications. This study aimed to investigate the frequency distribution of tympanostomy surgery, success rate, its complications and the demographic characteristics of patients during 2011-2017 in Sari, Iran. Materials and methods: This retrospective descriptive study was performed using data from the records of 512 patients who underwent VT surgery in Sari during 2011-2017. A checklist was used to collect the data and SPSS V24 was used for data analysis. Results: The most common complaint at the time of referral was hearing loss (38.3%). In 79%, bilateral VT was performed and 6.5% had complications after the operation. The most common complication was purulent otorrhea (4.1%). Postoperative success rate of VT was found to be 93%. Conclusion: Given the high success rate of VT surgery, this procedure could be a good method in treatment of hearing loss, acute recurrent middle ear infections, and the adverse effects of tonsillitis and allergy on middle ear.